Rock back phenomenon in 32 dogs that underwent tibial plateau levelling osteotomy - de Souza, Erica Siqueira; Minto, Bruno Watanabe [UNESP]; Luis, Jose Paulo Sales; Nobile, Matheus [UNESP]; Lins, Bruno Testoni [UNESP]; de Lucena, Dayvid Vianeis Farias [UNESP]; Gouveia, Marcelo Candido Portilho [UNESP]; Dias, Luis Gustavo Gosuen Goncalves [UNESP] (Czech Academy of Agricultural Sciences, 2021)
The aim of this study was to evaluate the postoperative temporal changes in the tibial plateau angle (TPA) after a tibial plateau levelling osteotomy (TPLO) in dogs. The TPA of thirty-two dogs were measured before surgery (TPA1), immediately after the TPLO (TPA2), and later at the healing of the osteotomy site (TPA3). Three observers carried out three TPA measurements for each patient at the time of the evaluation. TPA changes were observed over the bone healing (2.05 ± 3.05°); however, no statistical significance was noted when comparing TPA3 and TPA1. There were no statistical differences in the inter-observer measurements among TPA1, TPA2, and TPA3 (P > 0.05). The comparison between the preoperative TPA1 and the rock back showed a low positive correlation (S = 4 735.9, P = 0.471 5, r = 0.131 976 9). There was also a low positive correlation between the body weight (kg) and the change in the TPA during the bone healing (S = 4 581.8, P = 0.381, r = 0.160 234 7). Although changes in the TPA have been observed over the time of the bone healing, they were not influenced by the preoperative and postoperative TPA, or by the body weight. The magnitude of the variation in the TPA is not determined by the previous inclination or by the degree of rotation in the plateau.
Keywords: Cranial cruciate ligament; Orthopaedic surgery; Postoperative complication; TPA; TPLO